2014
DOI: 10.1002/hep.26735
|View full text |Cite|
|
Sign up to set email alerts
|

Forkhead box Q1 promotes hepatocellular carcinoma metastasis by transactivating ZEB2 and VersicanV1 expression

Abstract: Forkhead box Q1 (FoxQ1) is a master regulator of tumor metastasis. However, the molecular mechanism of FoxQ1 in regulating hepatocellular carcinoma (HCC) metastasis remains unknown. Here we report a novel function for FoxQ1 in modifying the tumor microenvironment to promote HCC metastasis. FoxQ1 expression was an independent and significant risk factor for the recurrence and survival in two independent cohorts totaling 1,002 HCC patients. FoxQ1 induced epithelial-mesenchymal transition (EMT) through the transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 33 publications
10
114
0
Order By: Relevance
“…It has previously been revealed that FOXQ1 is overexpressed in various types of human cancer, including colorectal (44), breast (45) and lung cancer (45) and HCC (46,47). Notably, high FOXQ1 expression levels were independent prognostic factors of HCC (46).…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been revealed that FOXQ1 is overexpressed in various types of human cancer, including colorectal (44), breast (45) and lung cancer (45) and HCC (46,47). Notably, high FOXQ1 expression levels were independent prognostic factors of HCC (46).…”
Section: Discussionmentioning
confidence: 96%
“…FOX proteins are a family of transcription factors, which regulate the expression of target genes involved in cellular differentiation, growth and proliferation (47). The family consists of the FOXA1, FOXA2, and FOXA3 proteins.…”
Section: Ar and Hbvmentioning
confidence: 99%
“…FOXQ1 induced metastasis through regulation of VersicanV1, which promoted tumorassociated-macrophages attraction. Also, similarly to colorectal cancer expression of FOXQ1 was regulated by the Wnt pathway in hepatocarcinoma (Xia et al, 2014).…”
Section: Hepatocarcinomamentioning
confidence: 91%
“…Cytogenetics FOXQ1 correlated with overall worse survival and higher recurrence Xia et al, 2014). Oncogenesis In hepatocarcinoma FOXQ1 directly activated the EMT transcription factor ZEB2.…”
Section: Hepatocarcinomamentioning
confidence: 96%